PECULIARITIES OF FUNCTIONAL MOBILITY AND STRENGTH OF NERVOUS PROCESSES IN ARMRESTLERS OF DIFFERENT LEVEL OF SPORTSMANSHIP - Nikulin I.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the indicators of functional mobility and the strength of nervous processes in armwrestlers of various levels of sportsmanship. Methods and structure of the study. The experiment involved arm wrestlers with the qualification "Master of Sports of Russia" (n=12), "Master of Sports of Russia of international class" (n=2) and "Honored Master of Sports" (n=1) in the amount of 15 athletes and engaged in mass sports arm wrestling. ranks from the third to the first - 15 people. The study used testing using the psychophysiological testing device UPFT-1/30 "Psychophysiologist". Testing of psychomotor abilities included the following indicators: functional mobility of nervous processes (FMNP), speed of nervous processes by measuring the dynamics of the pace of hand movement (tapping test). Results and conclusions. An analysis of the data on the functional mobility of the nervous processes of highly qualified athletes specializing in arm wrestling showed a significant predominance of indicators compared to arm wrestlers of mass sports categories. All examined highly qualified armwrestlers showed a very high functional mobility of nervous processes, the average score was 9.9. 50% of athletes of mass categories showed a very high functional mobility of nervous processes, the rest from very low to medium. The average score is 7.2. Data on the strength and lability of nervous processes by measuring the dynamics of the pace of hand movement showed an unreliable advantage in favor of qualified athletes, especially pronounced in the left hand.